Fully coupled atmosphere‐hydrology simulations for the central Mediterranean: Impact of enhanced hydrological parameterization for short and long time scales. (2nd November 2015) - Senatore, Alfonso; Mendicino, Giuseppe; Gochis, David J.; Yu, Wei; Yates, David N.; Kunstmann, Harald
Abstract: With the aim of developing a fully coupled atmosphere‐hydrology model system, the Weather Research and Forecasting (WRF) model was enhanced by integrating a new set of hydrologic physics parameterizations accounting for lateral water flow occurring at the land surface. The WRF‐Hydro modeling system was applied for a 3 year long simulation in the Crati River Basin (Southern Italy), where output from the fully coupled WRF/WRF‐Hydro was compared to that provided by original WRF model. Prior to performing coupled land‐atmosphere simulations, the stand‐alone hydrological model ("uncoupled" WRF‐Hydro) was calibrated through an automated procedure and validated using observed meteorological forcing and streamflow data, achieving a Nash‐Sutcliffe Efficiency value of 0.80 for 1 year of simulation. Precipitation, runoff, soil moisture, deep drainage, and land surface heat fluxes were compared between WRF‐only and WRF/WRF‐Hydro simulations and validated additionally with ground‐based observations, a FLUXNET site, and MODIS‐derived LST. Since the main rain events in the study area are mostly dependent on the interactions between the atmosphere and the surrounding Mediterranean Sea, changes in precipitation between modeling experiments were modest. However, redistribution and reinfiltration of local infiltration excess produced higher soil moisture content, lower overall surface runoff, and higher drainage in the fully coupled model. Higher soil moisture values in WRF/WRF‐Hydro slightly influenced precipitation and also increased latent heat fluxes. Overall, the fully coupled model tended to show better performance with respect to observed precipitation while allowing more water to circulate in the modeled regional water cycle thus, ultimately, modifying long‐term hydrological processes at the land surface. Key Points: Fully coupled model includes lateral surface and subsurface water fluxes Lateral redistribution increases soil moisture content compared to control run Precipitation and long‐term land surface hydrological processes are influenced